Comparison of angiography-guided vs. intra-vascular imaging-guiding percutaneous coronary intervention of acute myocardial infarction: a real world clinical practice - Lin, Ting-Yu; Chen, Ying-Ying; Huang, Shao-Sung; Wu, Cheng-Hsueh; Chen, Li-Wei; Cheng, Yu-Lun; Hau, William K.; Hsueh, Chien-Hung; Chuang, Ming-Ju; Huang, Wei-Chieh; Lu, Tse-Min (Frontiers in Cardiovascular Medicine, 2024)
The role of routine intravascular imaging in percutaneous coronary intervention (PCI) for acute myocardial infarction (AMI) has not been established. This retrospective, single-center study evaluated the clinical outcomes of PCI guided by various imaging modalities in AMI patients between 2012 and 2022. The mean follow-up (FU) was 12.9  1.73 months. The imaging modality-intravascular ultrasound (IVUS), optical coherence tomography (OCT), or angiography alone-was chosen at the operator's discretion. The primary endpoint was major adverse cardiac events (MACEs) (cardiovascular [CV] death, myocardial infarction [MI], target vessel revascularization). Of 1,304 PCIs, 47.5% (n=620) were guided by angiography alone, 37.0% (n=483) were IVUS-guided, and 15.4% (n=201) were OCT-guided. PCI guided by intravascular modalities correlated with lower 1-year MI (1.3%, P=0.001) and MACE (5.2%, P=0.036) rates. OCT-guided PCI correlated with lower rates of 1-year CV death (IVUS vs. OCT: 6.2% vs. 1.5%, P=0.016) and 1-year MACE (IVUS vs. OCT: 6.4% vs. 2.5%, P=0.032). Intravascular imaging modalities and diabetes were predictors of better and worse 1-year MACE outcomes, respectively. PCI guided by intravascular imaging modalities correlated with improved 1-year clinical outcomes when compared to angiography-guided alone PCI. OCT-guided PCI in AMI correlated with lower 1-year MACE rates than that associated with IVUS-guided PCI. Intravascular imaging modalities should be recommended for PCI in AMI, with OCT being considered when appropriate.